Sottobanco L'influenza delle tecnologie sul clima di classe - Soriani, Alessandro (Media e tecnologie per la didattica - Open Access, 2019)
Young pre-teens attending junior high schools are going through a very delicate period: they are not just engaged in a new and more complex school career but they are also engaged in their daily tasks of training and negotiating their identities and their roles in the different peer groups. This complex scenario is expanded by their first experiences, far from the eyes of adults, with technologies: tools that add, on the relational universe just described, an existential dimension that opens up new forms of communication mediated by digital contexts. Do technologies have an influence between on the relational dynamics that take place between students and their peers and between students and teachers? Which kind of influence? What dynamics are involved? What kind of technology is at stake? Is there a relationship of influence between the relationships mediated by the digital contexts and the social climate of a learning environment? What kind of influence? How much do students rely on digital-enriched relationships to satisfy their relationship needs? What perception do students and teachers have of relational dynamics mediated by digital contexts? And what role do they give to the school in this problem? To try to provide an answer to these questions, the volume presents a phenomenology of the witness of 21 teachers and 365 boys and girls belonging to two Italian and two French schools.